Integrating radiation protection criteria for radioactive waste management into remediation procedures in existing exposure situations after a nuclear accident. (23rd February 2018) - Sugiyama, Daisuke; Kimura, Hideo; Tachikawa, Hirokazu; Iimoto, Takeshi; Kawata, Yosuke; Ogino, Haruyuki; Okoshi, Minoru
Abstract: Experience after the accident at the Fukushima Daiichi nuclear power station has shown that there is a need to establish radiation protection criteria for radioactive waste management consistent with the criteria adopted for the remediation of existing exposure situations. A stepwise approach to setting such criteria is proposed. Initially, a reference level for the annual effective dose from waste management activities in the range 1–10 mSv should be set, with the reference level being less than the reference level for the ambient dose. Subsequently, the reference level for the annual effective dose from waste management activities should be reduced in one or more steps to achieve a final target value of 1 mSv. The dose criteria at each stage should be determined with relevant stakeholder involvement. Illustrative case studies show how this stepwise approach might be applied in practice.